Online corporate social responsibility reporting in the Croatian banking sector - Grudić Kvasić, Sanda (Mednarodna revija za javno upravo, 2016)
In the past few decades the concept of corporate social responsibility has been at the centre of interest in many areas of economic research, studied using different levels of analysis. This paper analyses corporate social responsibility at the level of organisation within the banking system, where the issue of corporate social responsibility disclosure comes under the spotlight with the emergence of the global economic crisis. The purpose of the study is twofold: to examine whether Croatian banks' online corporate social responsibility reporting depends upon their market share, and whether it focuses on community related information. Using website content analysis of all twenty-eight banks currently operating in the Croatian banking sector, corporate social responsibility disclosure is categorised in terms of themes (environment, human resources, customers and products, and community involvement). The research findings reveal that the level of Croatian banks' online CSR disclosure is largely dependent on banks' market share. On the other hand, results indicate that Croatian banks are mainly reporting on activities related to customers and products, followed by those which imply community involvement. Human resources and environmental initiatives receive the least amount of attention. The results of the study can be used to more deeply comprehend and understand banks' corporate social responsibility as a business philosophy that contributes to organisational performance and building trust between market participants.
Keywords: banke; banks; corporate social responsibility; Croatia; družbena odgovornost; gospodarske družbe; Hrvaška; online reporting; spletno poročanje